Development of a Physically Based Soil Albedo Parameterization for the Tibetan Plateau - Zheng, G. (2020)
The parameter values are calibrated and validated using the measurements from the Global Energy and Water Cycle Experiment–Asian Monsoon Experiment and the Coordinated Enhanced Observing Period Asia–Australia Monsoon Project (CAMP‐Tibet). Because few measurements of albedo are available from the TP, a transfer equation was built to estimate the parameter values through their inverse physical links with the soil composition. Compared with previous parameterizations, the parameter values from the transfer equation reduce the simulated mean bias and RMSE values by nearly 50%. Comparisons of the observed albedos and simulated values obtained using the new parameterization show that the correlation values are >0.5 and that the absolute errors (dimensionless) are within ±0.05. The new parameterization captures the diurnal and seasonal variations better than the previous schemes and shows that the diurnal and seasonal variations in soil albedo are controlled by the solar zenith angle and liquid soil moisture, respectively. This new parameterization scheme was incorporated into the Geomorphology‐Based Eco‐Hydrological Model and run for the CAMP‐Tibet stations. The inclusion of this new parameterization significantly improved the simulated surface energy budget in summer; the deviations in the upward shortwave radiation decreased by 81%, and the accuracy of the simulated Bowen ratio increased substantially.